2010
DOI: 10.1523/jneurosci.5694-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Calcium Signaling in ON and OFF Mouse Retinal Ganglion Cells

Abstract: Retinal ganglion cells (RGCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 38 publications
7
49
0
Order By: Relevance
“…Recent data has shown that while both ON and OFF RGCs express high voltage activated Ca 2+ channels, only OFF cells also express the LVA Ca 2+ channels (Margolis et al 2010). The results presented here show that many of the differences in intrinsic electrophysiology of ON and OFF cells can be explained on this basis.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Recent data has shown that while both ON and OFF RGCs express high voltage activated Ca 2+ channels, only OFF cells also express the LVA Ca 2+ channels (Margolis et al 2010). The results presented here show that many of the differences in intrinsic electrophysiology of ON and OFF cells can be explained on this basis.…”
Section: Discussionsupporting
confidence: 59%
“…Differences in response properties of ON and OFF RGCs are also shaped by their intrinsic electrophysiological properties, although only limited data are available (Margolis and Detwiler 2007;Margolis et al 2010Margolis et al , 2008. Margolis and Detwiler (2007) have examined the response of ON and OFF RGCs to currentclamp stimuli in mice when synaptic input was blocked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ON cells exhibit no endogenous activity and display none of the aforementioned phenomena [55]. Later, the same group determined the presence of a low-voltage activated (LVA) Ca 2+ channel in OFF cells that does not exist in ON cells [56]. A computational modeling study by Kamaneva et.…”
Section: Discussionmentioning
confidence: 99%
“…In the same WT OFF RGCs, rebound excitation, another intrinsic property, can be evoked by application of negative current in the absence of synaptic input and a role for low-voltage gated (LVA) Ca 2+ channels has been proposed (Margolis et al, 2010 . This could result from absence of GlyRα2-mediated inhibition of a tonic inhibitory input onto either the OFF RGC or its presynaptic OFF BC.…”
Section: Mechanisms That Contribute To Post Stimulus Rebound Excitatimentioning
confidence: 99%